Pengaruh Beban Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Sekretariat DPRD Kabupaten Wonogiri - Adisya S, Salma; Tri Haryanto, Aris; Riris S, Sri (Solidaritas, 2024)
The purpose of this research is to study how organizational culture and workload impact on employee performance in the Wonogiri Regency DPRD Secretariat office. This study used a quantitative approach. The population used was all employees of the Wonogiri Regency DPRD Secretariat Office. The sample used was a saturated sample with 31 respondents. Data collection used questionnaires distributed to collect research data. The tests used consisted of validity, reliability, classical assumption tests, multiple linear regression analysis tests, t tests, F tests, and coefficient of determination tests. The results showed that organizational culture and workload have a significant influence on employee performance in the Wonogiri Regency DPRD Secretariat office. With an Fcount value of 25.566 and a coefficient of determination of 0.646, the Workload and Organizational Culture variables together have a significant effect on employee performance at the Wonogiri Regency DPRD Secretariat office. This shows that these variables explain 64.6 percent of the employee performance variable, and other variables not included in this study amounted to 35.4%. Keywords: Workload, Organizational Culture, Employee Performance